From scandalization to normalization: conceptualizing the mainstreaming of far-right contestations in participatory processes - Gala Nettelbladt (European Planning Studies, 2022)
This paper is concerned with how the rise of far-right politics is normalized in local participatory processes. Starting with the observation that emerging accounts in planning scholarship scandalize the far right as an extrinsic threat to planning paradigms, I set out to challenge this line of thought, arguing that planning is no neutral safeguard of liberal democracy. I do so by drawing on social sciences literature on the issue of normalization, which captures how far-right ideologies are subsumed into the mainstream, i.e. how formerly tabooed topics of far-right discourse become `normal', shifting the boundaries of the `sayable'. To understand how normalization occurs within participatory processes, I mobilize the work of political theorist Olson, who theorizes how racism is ingrained in liberal democracy through the idea of `white democracy' – thus potentially enabling the legitimization of far-right contestations. Engaging a conversation with conceptual models of participation in planning, I analyse how `white democracy' manifests in two of the most central approaches to participation, communicative and agonistic planning perspectives. This is illustrated through the case of local citizens dialogues in Germany. Concluding this literature-based analysis, I propose three analytical and practical shifts to challenge the normalization of far-right contestations.
Keywords: 320; Agonistic planning; communicative planning; far right; local democracy; normalization; structural racism